OUTSOURCING OF R&D AND INNOVATION ACTIVITIES IN SMEs: EVIDENCE FROM SLOVENIA - Barbara Bradač Hojnik; Miroslav Rebernik (Economic Review)
This paper examines the outsourcing of research and development and of innovation activities in small and medium-sized companies (SMEs). As the results of these activities enable companies to achieve and sustain competitive advantage, it is crucial to manage them properly. As SMEs generally lack internal resources to perform R&D and innovation activities internally, is the outsourcing of these activities a viable solution for them? This paper examines the basic characteristics of outsourcing R&D and innovation activities in SMEs, based on a survey among Slovenian companies in the manufacturing and service industries. We tested five hypotheses. Empirical results show that one third of SMEs outsource R&D and innovation activities in different forms, and that small companies outsource these activities more often. The biggest share of SMEs partially outsources R&D and innovation activities, followed by SMEs that outsource all those activities, and by SMEs that perform R&D and innovate in co-operation with other firms. When comparing the type of R&D and innovation activities that are outsourced, the results show that SMEs mainly outsource experimental development, followed by basic research and applied research. However, they mostly outsource R&D and innovation activities to universities and independent research organisations and only occasionally to private organisations from industry and individual researchers.